Environmental factors associated with American cutaneous leishmaniasis in a new Andean focus in Colombia (2012)
ABSTRACT: Objective: To evaluate the environmental and ecological factors associated with Leishmania transmission and vector abundance in Chaparral, Tolima-Colombia.Methods: First, we compared the ecological characteristics, abundance of phlebotomies and potential reservoir hosts in the peridomestic environment (100 m radius) of randomly selected houses, between two townships with high and low cutaneous leishmaniasis incidence. Second, we examined peridomesticcorrelates of phlebotomine abundance in all 43 houses in the higher risk township.Results: The high transmission township had higher coverage of forest (23% vs. 8.4%) and shade coffee(30.7% vs. 11%), and less coffee monoculture (16.8% vs. 26.2%) and pasture (6.3% vs. 12.3%),compared to the low transmission township.Lutzomyia were more abundant in the high transmission township 2.5 vs. 0.2/trap/night.Lutzomyia longiflocosa was the most common species in both town-ships: 1021/1450 (70%) and 39/80 (49%). Numbers of potential wild mammal reservoirs were small,although four species were found to be infected with Leishmania(Viannia) spp. In the high transmission township, the overall peridomiciliary capture rate ofL. longiflocosa was 1.5/trap/night, and the abundance was higher in houses located nearer to forest (p= 0.30, P= 0.05).Conclusion: The findings are consistent with a domestic transmission cycle with the phlebotomies dependent on dense vegetation near the house.